Legal Protection for Women and Children in the Marriage Tradition of Muslim Communities - Sudirman; Intan Suria Hamzah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2024)
The Muslim community in East Java has a tradition of marriage that is believed to be a virtue. The tradition of marriage must provide legal protection for women and children. This study aims to (1) analyze the legal culture in the marriage tradition of the Muslim community in East Java and (2) find a model of preventive legal protection for women and children in the marriage tradition of the Muslim community in East Java. This research method is sociological research, which is expressed in quantitative data. Based on the research results, it is known that preventive legal protection for the Muslim community in East Java can be done by making the dowry an economic guarantee, providing monthly money, and the need for a prenuptial agreement. The Muslim marriage tradition in East Java typically sees wives joining their husbands' homes or establishing a shared residence, leading to a customary practice where wives may return to their own families upon divorce despite contributing to jointly owned homes. To address the economic vulnerabilities women and children face post-divorce, legal provisions should include stipulations on marriage dowry amounts, monthly financial obligations for wives, and requirements for prenuptial agreements to safeguard their interests. Implementing such protections would mitigate the financial repercussions experienced by wives and children following divorce.